Revision Total Hip Arthroplasty in Solid Organ Transplant Patients: A Propensity Score-Matched Cohort Study for Aseptic and Infected Revisions - Alex Upfill-Brown, MD, MSc; Christopher M. Hart, MD; Peter P. Hsiue, MD; Kadarius Burgess, BS; Clark J. Chen, MD; Amir Khoshbin, MD; Christos Photopoulos, MD; Alexandra I. Stavrakis, MD (Arthroplasty Today, 2022)
Background: Previous studies have demonstrated that solid organ transplant (SOT) patients undergoing primary total hip arthroplasty (THA) are at an increased risk of postoperative complications. The purpose of this study is to use a large, national database to investigate revision THA (rTHA) outcomes in SOT patients. Methods: Nationwide Readmissions Database (NRD) from 2010-2018 was used, and ICD-9 and ICD-10 codes were used to identify all patients who underwent rTHA, including those with history of SOT. Propensity score matching (PSM) was used to analyze rTHA outcomes in SOT patients comparted to matched controls. Separate analysis performed for patients undergoing rTHA for prosthetic joint infection (PJI) vs other causes. Results: A total of 414,756 rTHA, with 1837 of those being performed in SOT patients, were identified. Of these, 65,961 and 276 were performed for PJI in non-SOT and SOT patients, respectively. For non-PJI patients, SOT patients had higher 90-day all-cause readmission rates (24.0% vs 19.4%, P = .03) but lower rate for readmission related to rTHA (6.0% vs 9.2%, P = .03), but no difference readmission for specific rTHA complications, mortality (0.6% vs 1.3%, P = .20), or revision rTHA. Of PJI patients, SOT patients had no difference in overall 90-day readmission (38.6 vs 31.3%, P = .280), readmission for specific rTHA complications, re-revision, or mortality (4.7% vs 6.0%, P = .63). Conclusions: SOT patients undergoing rTHA for aseptic reasons are higher risk of overall readmission but lower risk of readmission related to rTHA than appropriately matched controls. SOT PJI patients undergoing had similar rates of readmission, mortality, and revision surgery compared to matched non-SOT PJI patients.